2022
DOI: 10.3389/fcimb.2022.1042977
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Shewanella putrefaciens as a novel pathogen of the largemouth bass (Micropterus salmoides) and histopathological analysis of diseased fish

Abstract: The largemouth bass (Micropterus salmoides) is an economically important aquaculture species in China, and its production has increased rapidly in recent years. Although Shewanella putrefaciens is known to infect several fish species, its role in infecting M. salmoides is relatively unknown. Here, we isolated a gram-negative bacterial strain (termed XX2021) from farmed largemouth bass. Based on the results of 16S rRNA sequencing and phylogenetic analyses, the isolate was identified as S. putrefaciens. The viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Previous studies have proven that ammonia can damage the liver and kidneys, which are essential organs for detoxification and waste removal [ 10 , 12 , 53 ]. Additionally, other studies have shown alterations in liver and kidney function in Shewanella -infected fish, and some have attributed these changes to virulence factors and toxins [ 22 , 25 , 33 ]. Therefore, the combined effects of both ammonia stress and Shewanella infection on O. niloticus may be more severe than the effects of either stressor alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have proven that ammonia can damage the liver and kidneys, which are essential organs for detoxification and waste removal [ 10 , 12 , 53 ]. Additionally, other studies have shown alterations in liver and kidney function in Shewanella -infected fish, and some have attributed these changes to virulence factors and toxins [ 22 , 25 , 33 ]. Therefore, the combined effects of both ammonia stress and Shewanella infection on O. niloticus may be more severe than the effects of either stressor alone.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous papers document histopathological changes in the liver and kidney of ammonia-exposed fish, the extent of which these changes vary based on the concentration and exposure period [ 10 , 56 , 98 , 99 ]. Additionally, different kinds of fish exhibit histological changes in their internal organs, mostly in the liver and kidneys [ 24 , 25 , 33 ]. These alterations are mainly due to the enzyme activity of Shewanella infection, ability to adhere to cells, and the release of cytotoxins [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diseased goldfish (Carassius auratus) showed lethargy, ascites and bulging eyes (Altun et al, 2014). There have been reports of the pathogenicity of S. putrfaciens in clownfish (largemouth bass) (Micropterus salmoides) with histopathological changes observed in the intestines, head of kidneys, spleen, and liver of diseased fish (Jiang et al, 2022). In addition, Shewanella algae were found to cause canker disease in American eel (Anguilla rostrata) (Wang et al, 2020) and black spot disease in white-leg shrimp (Penaeus vannamei) (Cao et al, 2010).…”
Section: Isolated and Identification Biofilm-forming Bacteriamentioning
confidence: 99%
“…Prevalence varies; however, it is not unexpected for up to 100% morbidity (Wildgoose, 2001) and 20% mortality (Pękala et al., 2015) to occur, especially if poor water quality and husbandry are co‐factors (Wildgoose, 2001). In recent years, there have been outbreaks of Shewanella putrefaciens ‐associated UD in wild eels (Esteve et al., 2017), barramundi (Erfanmanesh et al., 2019), gilthead seabream (Tapia‐Paniagua et al., 2018), Nile tilapia (Manal, 2017), rabbitfish (Saeed et al., 1990), largemouth bass (Jiang et al., 2022), European sea bass (Korun et al., 2009), rainbow trout (Pękala et al., 2015), common carp (Pękala et al., 2015), and koi carp (Cocchi et al., 2018). In these studies, S. putrefaciens was identified as an opportunistic fish pathogen capable of inducing a range of lesions (particularly UD) during periods of physiological stress or immunocompromise (Kozinska & Pekala, 2004).…”
Section: Introductionmentioning
confidence: 99%